Prostitution and the ends of empire : scale, governmentalities, and interwar India - Legg, Stephen (Duke University Press, 2014)
A theoretically sophisticated historical account of the ways prostitution was managed and regulated in the interwar period in colonial India. Stephen Legg shows that such regulation was outsourced by the government to reformatist civil societies, such as the Association for Moral and Social Hygiene. He tracks the ways that government policy and popular opinion shifted from acceptance of prostitution, to segregation and regulation, and, finally, to suppression and abolition.